Metal Oxide based Chalcogenides Heterostructure Thin Film Photoanodes for Photoerochemical Solar Hydrogen Generation - Ho, Soon Min; Mahadik, M.A; Jang, J.S; Singh, V.N (2018)
Thin films have been used for many applications. Hydrogen production from solar water splitting has been considered as a key solution to the energy and environmental issues. The tuned band gap alignments in metal chalcogenides/metal oxides heterostructure enable efficient separation of photogenerated electrons and holes, leading to the effective hydrogen production. We sensitize these structures by hydrothermal methods and evaluate the performance toward hydrogen generation. This work shows a brief overview of photoelectrochemical hydrogen production, progress and ongoing sprints. Here, different metal chalcogenides were deposited on metal oxides (TiO2 and Fe2O3) in order to improve the photoelectrochemical performance by reducing recombination of photogenerated electron–hole pairs and facilitate hole transport at the metal chalcogenides/metal oxides/electrolyte interface. The study includes chalcogenides/metal oxides heterostructure designs and electrochemistry and solar hydrogen generation are brought together, illustrating the promise and challenge of photoelectrochemistry.